Mid-nineteenth century writers : Eliot, De Quincy, Emerson (Marison : Published for the Department of English by the University of Wisconsin Press, 1976)
Contents. Wolfe, T.P. The inward vocation: an essay on George Eliot's Daniel Deronda.--Maniquis, R.M. Lonely empires: personal and public vision of Thomas de Quincey.-- La Rosa, R. C. Necessary truths : the poetics of Emerson's Proverbs.
Keywords: English literature -- 19th century -- History and criticism; Eliot, George, pseudo., i.e. Marian Evans, afterwards Cross, 1819-1880. Daniel -- Deronda; De Quincey, Thomas, 1785-1859 -- Criticism and interpretation; Emerson, Ralph Waldo, 1803-1882 -- Criticism and interpretation